A randomised controlled comparison of tiotropium and ipratropium in the treatment of chronic obstructive pulmonary disease. Issue 4 (1st April 2000) - van Noord, J A; Bantje, Th A; Eland, M E; Korducki, L; Cornelissen, P J G
Abstract : BACKGROUND: A study was undertaken to evaluate and compare the efficacy and safety of tiotropium and ipratropium during long term treatment in patients with stable chronic obstructive pulmonary disease (COPD). METHODS: 288 patients of mean (SD) age 65 (8) years and forced expiratory volume in one second (FEV1 ) 41 (12)% predicted participated in a 14 centre, double blind, double dummy, parallel group study and were randomised after a run in period of two weeks to receive either tiotropium 18 μg once daily from a dry powder inhaler (HandiHaler; two thirds of patients) or ipratropium 40 μg four times daily from a metered dose inhaler (one third of patients) for a period of 13 weeks. Outcome measures were lung function, daily records of peak expiratory flow (PEF), and the use of concomitant salbutamol. FEV1 and forced vital capacity (FVC) were measured one hour before and immediately before inhalation (mean value of the two measurements on test day 1 was the baseline value while on all other test days it was known as the trough FEV1 and FVC), and 0.5, 1, 2, 3, 4, 5, and 6 hours after inhalation of the study drug on days 1, 8, 50, and 92. RESULTS: During treatment tiotropium achieved a significantly greater improvement than ipratropium (p<0.05) in trough, average, and peak FEV1 levels and in trough and average FVC levels. The trough FEV1 response on days 8, 50, and 92 ranged between 0.15 l (95% CI 0.11 to 0.19) and 0.16 l (95% CI 0.12 to 0.20) for tiotropium and between 0.01 l (95% CI –0.03 to 0.05) and 0.03 l (95% CI 0.01 to 0.07) for ipratropium. The trough FVC response on days 8, 50, and 92 ranged between 0.34 l (95% CI 0.28 to 0.40) and 0.39 l (95% CI 0.31 to 0.47) for tiotropium and between 0.08 l (95% CI 0.00 to 0.16) and 0.18 l (95% CI 0.08 to 0.28) for ipratropium. On all test days tiotropium produced a greater improvement in FEV1 than ipratropium starting three hours after inhalation (p<0.05). During treatment weekly mean morning and evening peak expiratory flow (PEF) was consistently better in the tiotropium group than in the ipratropium group, the difference in morning PEF being significant up through week 10 and in evening PEF up through week 7 of treatment (p<0.05). The use of concomitant salbutamol was also lower in the tiotropium group (p<0.05). The only drug related adverse event was dry mouth (tiotropium 14.7%, ipratropium 10.3% of patients). CONCLUSIONS: Tiotropium in a dose of 18 μg inhaled once daily using the HandiHaler was significantly more effective than 40 μg ipratropium four times daily in improving trough, average, and peak lung function over the 13 week period. The safety profile of tiotropium was similar to ipratropium. These data support the use of tiotropium as first line treatment for the long term maintenance treatment of patients with airflow obstruction due to COPD.